The existence of the Chirano Gold Mine Limited and its effect on the livelihood of the Chirano Concession Area - Darko, Eric (2012)
A thesis submitted to the Department of Materials Engineering of the College of Engineering, in partial fulfilment of the requirements for the degree of Master of Science, in Environmental Resources Management, June-2012